Solusi Al-Qur’an Dalam Mewujudkan Ketahanan Keluarga Melalui Pendidikan Karakter - Buchori, Ahmad; Lestari, Tri Kurniah; Mutmainnah, Nurul; Lail, Fitryani; Zaidir, Zaidir (LP2M Universitas Islam Ahmad Dahlan, 2024)
This research aims to find out how the Koranic solution in realizing family resilience through character education. This type of research uses a literature review with a narrative review design, namely looking for articles related to the koran's solution to realizing family resilience through character education that has been published. Existing journals and references obtained the results that Qur’an-based character education means instilling the values contained in the Qur’an as a guide. As the Prophet made the Qur'an as his character according to the meaning of the Qur'an surah Al Qalam verse 4. The character education in question can be used as a solution in building family resilience, where disputes and arguments that occur continuously in the family environment become the main factor in divorce cases can be minimized with Qur'anic values such as mutual respect, mutual respect, mutual love, mutual help and mutual attention to each family member.